Community participation in education: A case study of the Boards of Trustees’ experience in Anand District - Ms. Rupalben Bhupendrabhai Patel (Vidhyayana - An International Multidisciplinary Peer-Reviewed E-Journal - ISSN 2454-8596, 2021)
The present study examines the case of community participation in education in Anand district and its experience in developing Board of Trustees (BOTs) in public schools. Through field surveys with members of the Board of Trustees, their perceptions of the BOT’s efficiency, effectiveness, and problems in the context of the theoretical literature and other international experiences are analyzed. The main findings point to the fact that Anand district is consistent with the ongoing pattern in education and calls for increasing shared responsibility for provision. Although respondents were generally optimistic about potential opportunities for BOTs to improve the quality of the educational process, their current level of assessment of actual effectiveness was not uniform. Obviously, more needs to be done to transform the experience of establishing and managing BOT from just one form of pseudo participation to becoming more real.